1997
DOI: 10.1002/eji.1830271124
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide pathway is induced by FcεRI and up‐regulated by stem cell factor in mouse mast cells

Abstract: Murine stem cell factor (SCF) induces the differentiation of mucosal mast cells (MMC) into connective tissue mast cells (CTMC) and potentiates mediator release induced by aggregation of high-affinity IgE receptors (Fc epsilon RI). In the present work, we investigated the effect of Fc epsilon RI aggregation on nitric oxide (NO) pathway induction in the different subsets of mast cells, as well as the contribution of SCF in this induction. Inducible NO synthase (iNOs) expression was not evidenced in non-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 44 publications
0
32
2
1
Order By: Relevance
“…The source of NO in enteropathy has not been identified but a number of cells including epithelial cells, macrophages, and mast cells have been implicated (9,(43)(44)(45). Epithelial cells are the first point of host contact for invasive intestinal pathogens and may initiate mucosal inflammatory responses via production of proinflammatory cytokines and mediators including NO (8,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of NO in enteropathy has not been identified but a number of cells including epithelial cells, macrophages, and mast cells have been implicated (9,(43)(44)(45). Epithelial cells are the first point of host contact for invasive intestinal pathogens and may initiate mucosal inflammatory responses via production of proinflammatory cytokines and mediators including NO (8,43).…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells have also been shown to induce intestinal pathology by a number of mechanisms including the release of mediators such as cytokines, histamine, and NO (32)(33)(34)49). There is also evidence that mast cells have the ability to synthesize and release NO derivatives through their own expression of iNOS induced by IgE immune complexes (44). Furthermore, iNOS has been shown to be crucial in allergic inflammatory processes by regulating the activation and degranulation of mast cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…The present observation is basically in line with earlier findings of TNF-mediated enhanced production of NO in cultured peritoneal and intestinal mast cells (Bissonnette et al, 1991), however, NO production was at that time not attributable to a certain NOS isoform. There is inconsistent information about NOS isoenzyme expression in mast cells of different organs: positive bNOS immunoreactivity has been reported for human skin mast cells (Shimizu et al, 1997), whereas both mouse myometrial (Huang et al, 1995) and connective tissue mast cells (Bidri et al, 1997) showed iNOS expression after hormonal or antigen stimulation. Further studies should address the issue of whether the up-regulation of eNOS in response to LPS in mast cells as opposed to other cell types is a lung-specific finding or is representative for mast cells of other organ origin.…”
Section: Ermert Et Almentioning
confidence: 99%
“…Indeed, intracellular ROS generation has been reported for RPMC (17)(18)(19), a mouse mast cell line (20), RBL-2H3 cells, and mouse bone marrow-derived mast cells (21). To date, no studies have been performed with human mast cells.Reports from several groups claim that mast cells produce [22][23][24][25][26], although again, studies from our own laboratory (27-29) have provided contradictory evidence. Salvemini et al (22) reported the release of a NO-like activity from rat peritoneal mast cells, although their preparations contained up to 15% macrophages, a known source of NO.…”
mentioning
confidence: 91%
“…Salvemini et al (22) reported the release of a NO-like activity from rat peritoneal mast cells, although their preparations contained up to 15% macrophages, a known source of NO. Bidri et al (23) reported expression of the inducible form of NO synthase (NOS2) and nitrite production by mouse bone marrow-derived mast cells, whereas Gilchrist et al (24 -26) have demonstrated inducible or constitutive NOS expression, nitrite production, and intracellular NO-induced DAF fluorescence in activated RPMC and the human tumor-derived HMC-1 and LAD2 mast cell-like lines. In contrast, we found that interferon (IFN)-␥ stimulated or spontaneous NO production by rat or mouse peritoneal mast cells diminished as mast cells were progressively purified, such that even in preparations that contained 98 -99% mast cells, the NO production could be fully accounted for by the residual 1-2% non-mast cells (27,28).…”
mentioning
confidence: 99%